Economic and Environmental Aspects of the Development of Renewable Energy in Kazakhstan - BAKTYMBET, Aisara S.; UKUBASSOVA, Galiya S.; BAKTYMBET, Saule S.; BAKTYMBET, Assem S.; BAKIRBEKOVA, Aigul M. (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020DO - 10.14505//jemt.v11.5(45).01, 2020)
One of the key tasks for the world community is the development of energy, which is one of the fundamental components of the economy. However, one cannot deny the fact that energy is the main factor in environmental pollution, which leads to the constant search for such types of energy sources that would have a positive impact on the economic development of territories and favourably affect the environment, alternative sources to traditional ones. Currently, there is an energy transformation, the main condition of which is the development of alternative energy technologies. One of the prospects for the economic and environmental development of the territories is the efficient use of renewable energy sources, which are becoming increasingly important in the world community and the global energy balance, and are becoming a substitute resource for traditional fossil energy resources. The article aims to analyse the economic and environmental aspects of the development of renewable energy in Kazakhstan and identify the main prospects. In the framework of the study, the concept of renewable energy sources, their main types are defined, the opinion of various authors regarding the development of renewable energy sources is described, the main directions aimed at stimulating the development of renewable energy are considered. The development of renewable energy in Kazakhstan in comparison with other countries (USA, China, Germany, Russia) is considered, the main problems are identified, the prospects for the development of renewable energy are also considered. The prospects for further research are determined by the subsequent study of the development of renewable energy sources, taking into account economic and environmental aspects. The article is of practical value in the framework of generalising data on the development of renewable energy in Kazakhstan and foreign countries.